Vector network equilibrium problems with capacity constraints of arcs - Xu, Y.; Li, S.; Teo, Kok Lay (ELSEVIER, 2012)
In this paper, we study a (weak) vector equilibrium principle with capacity constraints ofarcs and common arcs in some different paths. We obtain some necessary and sufficientconditions for a (weak) vector minimum cost flow. By virtue of a (weak) D-equilibrium principle, we also derive some necessary and sufficient conditions for a weak vector equilibrium flow.